Development and psychometric testing of a new instrument to measure the caring behaviour of nurses in Italian acute care settings. (15th August 2017) - Piredda, Michela; Ghezzi, Valerio; Fenizia, Elisa; Marchetti, Anna; Petitti, Tommasangelo; De Marinis, Maria Grazia; Sili, Alessandro
Abstract: Aim: To develop and psychometrically test the Italian‐language Nurse Caring Behaviours Scale, a short measure of nurse caring behaviour as perceived by inpatients. Background: Patient perceptions of nurses' caring behaviours are a predictor of care quality. Caring behaviours are culture‐specific, but no measure of patient perceptions has previously been developed in Italy. Moreover, existing tools show unclear psychometric properties, are burdensome for respondents, or are not widely applicable. Design: Instrument development and psychometric testing. Method: Item generation included identifying and adapting items from existing measures of caring behaviours as perceived by patients. A pool of 28 items was evaluated for face validity. Content validity indexes were calculated for the resulting 15‐item scale; acceptability and clarity were pilot tested with 50 patients. To assess construct validity, a sample of 2, 001 consecutive adult patients admitted to a hospital in 2014 completed the scale and was split into two groups. Reliability was evaluated using nonlinear structural equation modelling coefficients. Measurement invariance was tested across subsamples. Results: Item 15 loaded poorly in the exploratory factor analysis ( n = 983) and was excluded from the final solution, positing a single latent variable with 14 indicators. This model fitted the data moderately. The confirmatory factor analysis ( n = 1018) returned similar results. Internal consistency was excellent in both subsamples. Full scalar invariance was reached, and no significant latent mean differences were detected across subsamples. Conclusion: The new instrument shows reasonable psychometric properties and is a promising short and widely applicable measure of inpatient perceptions of nurse caring behaviours.